Formation of the brand of a military university as a condition for increasing its competitiveness in the modern market of educational services - L. A. Saenko; Yu. S. Tsygankova (Вестник Северо-Кавказского федерального университета, 2023)
The sharply increased demand for educational services in the higher education market has intensified the competition between universities. This has led to the popularity of introducing marketing technologies into the system of management tools of educational organizations that contribute to increasing their level of competitiveness. The previous communication methods were no longer enough to promote the university to the forefront, in connection with which the issues of creating its unique brand were updated. This problem has not bypassed military universities, which also need to increase their competitiveness in the educational market through the formation and development of the brand of a modern military institution. The purpose of the article is to identify effective ways to form a brand of a military university, allowing it to effectively compete with other educational institutions in the modern educational space. In the course of the study, specific features of branding in the field of education were identified, based on which the main ways to improve the tools for promoting the brand of a military university were proposed, allowing it to effectively compete with other educational organizations: focus on functioning in a system with a rich historical heritage and moral content; continuous monitoring of the professional path of university graduates; maintaining a decent level of professional training of the teaching staff; formation of comfortable learning conditions with high-quality material and technical base; creation of a favorable environment for the active life of students.